Enhancing sustainability practices in Malaysian food manufacturing SMEs: the mediating effect of innovation capability - Latip, Malisah; Sharkawi, Ismawati; Mohamed, Zainalabidin (John Wiley and Sons, 2025)
Sustainability is crucial in the food manufacturing business strategy, driven by environmental considerations and market demands. This study examines the influence of organizational support, human resource quality, and innovation capability on the intention to adopt sustainability practices among Malaysian food manufacturing SMEs while investigating innovation capability's mediating role. Grounded in the resource-based view (RBV), natural resource-based view (NRBV), and triple bottom line (TBL) frameworks, the study focuses on understanding factors influencing intentions rather than actual implementation or outcomes. A survey of 367 SME owner-managers was conducted via e-mail. Structural equation modeling analysis showed that all three factors significantly influence the intention to adopt sustainability practices, with innovation capability partially mediating these relationships. These findings expand the theoretical understanding of sustainability adoption in SMEs, validating innovation capability's mediating role in the food manufacturing sector. For academia, the study contributes to the literature on sustainability in SMEs. Policymakers can use these results to develop initiatives supporting sustainable practices, such as funding for sustainable technology or environmental education. For SME owner-managers, the findings encourage viewing investments in human resources and innovation capabilities as catalysts for fostering intentions toward sustainability.